Lack of expression of hepatitis C virus core protein in human monocyte derived dendritic cells using recombinant semliki forest virus (2019)
ABSTRACT: Hepatitis C Virus belongs to the Flaviviridae family. One proposed mechanism of HCV persistence in the ability to infect hematopoietic cells, including Dendritic cells (DCs). HCV infection of DCs could impair their functions that represent one of the mechanisms, thus hampering viral clearance by the host immune system. Among HCV-encoded proteins, the highly conserved Core protein has been suggested to be responsible for the immunomodulatory properties of this Hepacivirus. Recombinant viral vectors expressing the HCV Core protein and allowing its transduction and therefore the expression of the protein into DCs could be useful tools for the analysis of the properties of the Core protein. Vaccinia Virus and retrovirus have been used to transduce human DCs. Likewise, gene transfer into DCs using Semliki Forest Virus has been reported. This study aimed to express the HCV Core protein in human monocyte-derived DCs using an SFV vector, in which the subgenomic RNA encoding the structural proteins was replaced by the HCV Core sequence and then analyze the effects of its expression on DCs functions